(3TQM GdebOeI GdLhdjI aj GdfMhs - (3CHh Ydj YeQ Hf eMeO Hf YeQ GdTdhHjfs; (3YjSi Hf YHO GdYRjR Hf jddHNJ GdLRhdj GdHQHQj GdeQGcTj, CHh ehSi,J (B607 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh Ydi TgQ HGdTdhHjf (B: (3GdMeO ddg GdeJaVd YdfjG HCaVd GdfYe SCdfi HYV ef jcQe Ydi Cf GcJH dg Ydi GdebOeI GdeVGaI s
(3BNQgG (B:s
(3jfJgi CKfGA bhdg (B: (3MQha GdWQajf hbhd GdTGQM (B: (3jQjO HGdWQajf WQai Gdae hefgG GdMdb hGdTbGf dge JUGQja s
(3HChdgG JMHjS ef CHj GdQHjY SdjeGf GdOcGdi Ydi NRGfI GdbQhjjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B104 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B27s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdfMhs